2015
DOI: 10.3390/ma8105327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Modification on the Microstructure and Thermo-Mechanical Properties of Bamboo Fibers

Abstract: The objective of this study is to investigate the effect of surface treatment on the morphology and thermo-mechanical properties of bamboo fibers. The fibers are subjected to an alkali treatment using 4 wt % sodium hydroxide (NaOH) for 1 h. Mechanical measurements show that the present concentration has an insignificant effect on the fiber tensile strength. In addition, systematic experimental results characterizing the morphological aspects and thermal properties of the bamboo fibers are analyzed by scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 36 publications
5
81
0
3
Order By: Relevance
“…It is anticipated therefore that fiber surface modification is needed to decrease fiber polarity and improve interfacial compatibility . Indeed, alkaline treatment has been justified as the most popular and lowest cost candidate for surface modification . This method can eliminate those non‐cellulosic components, such as wax, hemicellulose, and other inorganic impurities, and then it results in an effective surface area increment available for superior adhesion with the matrix .…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated therefore that fiber surface modification is needed to decrease fiber polarity and improve interfacial compatibility . Indeed, alkaline treatment has been justified as the most popular and lowest cost candidate for surface modification . This method can eliminate those non‐cellulosic components, such as wax, hemicellulose, and other inorganic impurities, and then it results in an effective surface area increment available for superior adhesion with the matrix .…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed in another study and was described as a result of the increase in the length-to-diameter ratio during the performed modification. Therefore, according to the authors, the evaporation of moisture was facilitated [60] which contributed to the fall in enthalpy values.…”
Section: Dsc Investigationmentioning
confidence: 99%
“…Ionic liquids have been used as a reaction medium for modifying cellulose using urea, phthalic anhydride (PA), maleic anhydride (MA) and butyl glycidyl ether (BGE). Previous experiments have shown that the hydrogen bonding interactions decrease and that anhydride groups have a higher reaction activity with hydroxyl groups [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first stage involved moisture evaporation at around 150 o C, measured at 4wt% loading. This is followed by the decomposition of the hemicellulose at around 300 o C [28,29]. Hemicellulose can be categorized as the most reactive and easily degrade constituent compared to cellulose and lignin.…”
Section: Fig 1 Tga For [Cneim][br]mentioning
confidence: 99%